Analysis of the Success Factors in the Implementation of the Street Vendor Management Policy in the Food Colony Area of Pamekasan Regency - Syafiril Ajmal Yanotama; Rosyidatuzzahro Anisykurlillah (Darul Yasin Al Sys, 2026)
The relocation of street vendors is a strategic policy adopted by the Government of Pamekasan Regency to improve public space management and provide a more organized business environment through the development of the Food Colony. However, its implementation has faced challenges related to vendor acceptance and the sustainability of economic activities at the relocation site. This study aimed to analyze the implementation of the street vendor relocation policy using George C. Edwards III’s framework, encompassing communication, resources, disposition, and bureaucratic structure. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation involving the Department of Cooperatives, Small and Medium Enterprises, and Manpower; the Municipal Police; the Department of Transportation; and relocated street vendors. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that policy communication was facilitated through socialization, mediation, and persuasive approaches, enabling information to be conveyed clearly to the affected vendors. The resource dimension was supported by adequate facilities and interagency coordination, while policy implementers demonstrated a strong commitment to the relocation process. Nevertheless, several vendors remained reluctant to relocate because of concerns regarding declining income, leading some to continue operating outside the designated Food Colony area. The bureaucratic structure functioned effectively through an integrated implementation team and clearly defined institutional responsibilities. The study concludes that the relocation policy has been procedurally well implemented, but its substantive effectiveness remains constrained by the limited economic sustainability of relocated vendors. These findings contribute to street vendor management policy by demonstrating that procedural compliance must be accompanied by strategies that strengthen vendors’ economic viability. Enhancing promotional activities, improving the attractiveness of the Food Colony, and enforcing regulations consistently are therefore essential for optimizing policy outcomes.